A regional approach to human security in East Asia: Global debate, regional insecurity and the role of civil society - TANG, James T. H. (Institutional Knowledge at Singapore Management University, 2004)
The concept of human security as a new paradigm presents a particular challenge for East Asia. While the region experienced dramatic political, economic and social transformations in the last few decades, much of the region’s key security concerns are state-focused. In fact East Asian regional security structures that are products of the Cold War era have remained largely intact.